The effects of alternative free trade agreements on Peru: Evidence from a global computable general equilibrium model - Bouët, Antoine; Mevel, Simon; Thomas, Marcelle (International Food Policy Research Institute, 2008)
By using a global computable general equilibrium model, this report analyzes the impact of various pending free trade agreements for Peru. In December 2007, a Peru–United States free trade agreement (FTA) was finally ratified by the U.S. Congress, replacing the Andean Trade Promotion and Drug Eradication Act, which awarded Peru and other Andean countries nonreciprocal preferential tariffs. A Peru–European Union (EU27) FTA is also being negotiated in the context of Peru’s participation in the integration of the Andean Community (CAN). Finally, as of October 2008 Peru is concluding negotiations for a free trade agreement with China, its third major trading partner after the United States and the EU27. Although these agreements are expected to improve market access, their impact on the economic welfare of the beneficiary countries is dependent on the countries’ structure of current tariffs and trade and the extent to which the new agreements result in trade diversion versus trade creation. The analysis shows that specific features of Peru’s trade and tariff structures make the country a better candidate for a South-South FTA with China than for North-South FTAs with the United States or the EU27.